2013
DOI: 10.3390/nu5041024
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Toxicity from a Misformulated Dietary Supplement, Adverse Health Effects, and the Temporal Response in the Nail Biologic Monitor

Abstract: Use of dietary supplements in the U.S. has increased steadily over the last 25 years. While misformulation is uncommon, the consequences can be serious. A March 2008 voluntary market recall removed supplement products responsible for the most serious selenium toxicity outbreak that has occurred in the U.S. We quantified selenium concentrations in the misformulated supplement products, measured the temporal response in the nail biologic monitor, and associated exposure to self-reported selenosis symptoms. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 72 publications
3
51
2
1
Order By: Relevance
“…First, its limited statistical power, which was a consequence of the difficulties in finding volunteers available for the study from the general population and of the large amount of resources required for speciation analysis. This reduced the statistical stability of the point estimates, though the coherence across age groups and sexes of some results and the association of serum Se species with dietary supplements and smoking status, as expected [82,83], appear to confirm the reliability of study results [84,85].…”
Section: Discussionmentioning
confidence: 74%
“…First, its limited statistical power, which was a consequence of the difficulties in finding volunteers available for the study from the general population and of the large amount of resources required for speciation analysis. This reduced the statistical stability of the point estimates, though the coherence across age groups and sexes of some results and the association of serum Se species with dietary supplements and smoking status, as expected [82,83], appear to confirm the reliability of study results [84,85].…”
Section: Discussionmentioning
confidence: 74%
“…Researches have pointed out that the use of supplements is somewhat uncertain in terms of efficiency due to the Se forms added in commercial supplements, as well as because the supplements are usually unevenly distributed among different population groups (Pietinen et al, 2010). In addition, Aldosary et al (2012) and Morris and Crane (2013) reported several cases of Se intoxication in people due to the intake of these supplements. Industrially fortified foods and supplements mostly contain inorganic Se forms (selenate and/or selenite).…”
Section: How To Increase Selenium Intake By Humansmentioning
confidence: 99%
“…Furthermore, strong evidence shows different biological activities of the various organic and inorganic forms of selenium (Hazane-Puch 2013; Rayman 2008a; Vinceti 2009; Vinceti 2013c; Weekley 2013), suggesting the opportunity to better char-acterise the specific toxicological and nutritional properties of each selenium species in humans, in animals and in the environment. Recent publications have questioned the adequacy of the current upper ’safe’ limit of intake (Jerome-Morais 2011; Morris 2013; Moyad 2012; Rocourt 2013; Sacco 2013; Vinceti 2009; Vinceti 2013b) and have espoused the need to set different limits for the many different sources of organic and inorganic selenium.…”
Section: Introductionmentioning
confidence: 99%